2017
DOI: 10.3201/eid2304.160773
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of Scarlet Fever, South Korea, 2008–2015

Abstract: The incidence rate for scarlet fever in South Korea is rising. During 2008–2015, we collected group A Streptococcus isolates and performed emm and exotoxin genotyping and disk-diffusion antimicrobial tests. Scarlet fever in South Korea was most closely associated with emm types emm4, emm28, emm1, and emm3. In 2015, tetracycline resistance started increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 14 publications
2
44
1
Order By: Relevance
“…A substantial increase in the incidence of scarlet fever has been seen in east Asia and the UK since 2008. 1,3,[5][6][7] This study has shown that China also had a striking increase in the incidence of scarlet fever in 2011 that coincided with a resurgence of the disease in Hong Kong and South Korea, whereas England did not have an increase in incidence until 2014. In China, the average annual incidence of scarlet fever in the period after the upsurge, between 2011 and 2016, was double that reported before the upsurge .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…A substantial increase in the incidence of scarlet fever has been seen in east Asia and the UK since 2008. 1,3,[5][6][7] This study has shown that China also had a striking increase in the incidence of scarlet fever in 2011 that coincided with a resurgence of the disease in Hong Kong and South Korea, whereas England did not have an increase in incidence until 2014. In China, the average annual incidence of scarlet fever in the period after the upsurge, between 2011 and 2016, was double that reported before the upsurge .…”
Section: Discussionmentioning
confidence: 84%
“…Although the predominant group A streptococcus emm gene types are varied in China (emm12, emm1), [16][17][18] South Korea (emm3, emm28), 6 and England (emm3, emm12), 1,19 all these countries had the same challenges of scarlet fever re-emergence. Scientists have found that one of the possible causes of the scarlet fever upsurge is that S pyogenes is expanding from a single clonal lineage to multiclonal lineages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the effective antibiotics, hygiene and nutrition has been improved in the past decade, there were a sudden increase in the incidence of the scarlet fever in Asia [3][4][5][6][7]. After implementation of two-child policy from 2011, scarlet fever is an increasing threat to the growing child population in China, which had a sudden increase in the number of susceptible children [8].…”
Section: Introductionmentioning
confidence: 99%